A Problem for Christian Materialism - Knuths, Elliot Jon (European journal for philosophy of religion, 2018)
This piece raises a new challenge for Christian materialist accounts of human persons. Revisiting one of the perennial challenges for Christian materialism, explaining the metaphysical compatibility of resurrection and the life everlasting with materialist metaphysics, I argue that resuscitation phenomena reported in scripture undermine van Inwagen's and Zimmerman's attempts to reconcile resurrection and materialism. Although this challenge to Christian materialism is not insurmountable, it provides good reason to reject several of the most serious Christian materialist projects and offers a reason for Christians to consider alternatives to materialism.